GASTROINTESTINAL AND RENAL COMPLICATIONS IN BURNED PATIENTS - HABERAL, M; OZDEMIR, A; BAYRAKTAR, U; ONER, Z; BILGIN, N (SPRINGER VERLAG, 1993)
During an 11 year period of burn treatment, from 1 January 1979 until 31 December 1989, a total of 915 burn injury patients were admitted to our center. All patients were treated with the Parkland formula. During the treatment of these burn patients, 24 (2.6%) encountered gastrointestinal complications (GI), with 22 of them having upper GI complications. Vagotomy+ pyloroplasty or vagotomy+gastrojejunostomy, along with oversewing, was performed in four patients with massive bleeding, terminating the bleeding. Eighteen of the 22 patients with upper GI bleeding died. Four of these deaths were due to massive bleeding, and the remaining were due to septic complications. Nineteen (2%) of the 915 burn patients admitted to our center during this time were major burn patients, requiring dialysis treatment due to acute renal failure. The burn injuries in these patients varied statistically (P-0.01). Reasons for acute tubular necrosis (ATN) in the renal failure patients was either multiple organ failure (MOF) or sepsis. The mortality mte in patients requiring dialysis was 78.9% in acute renal failure patients; 100% in flame burned patients and 60% in electrically burned patients.
Keywords: BURN INJURY; TREATMENT; GASTROINTESTINAL AND RENAL COMPLICATIONS; MORTALITY; Surgery